Numerical study on the mechanical stress and mechanical failure of planar solid oxide fuel cell. (1st November 2018) - Fang, Xiurong; Lin, Zijing
Highlights: A solid mechanics model combined with fully coupled flow-heat-mass-current transport. Simulations based on and validated by the newest experimental data. Effects of Ni content and oxidation state on stress and failure probability revealed. Importance of reducing temperature gradient for the increased lifetime illustrated. Abstract: Damage by mismatch of thermal expansion coefficients and temperature gradient is a major factor limiting the long-term stability of solid oxide fuel cell (SOFC). Numerical simulations are performed to provide in-depth information about the mechanical stress, mechanical failure probability and creep strain rate of planar SOFC. The dependences of the mechanical performance of SOFC on the Ni content and its oxidation state as well as the temperature ( T ) are revealed. Based on a realistic T -profile obtained by multi-physics simulation of a SOFC stack model, it is shown that the maximum creep strain rate of the operating stack is 40% higher than that of an isothermal stack with the same average T . A T -distribution deduced from a multi-physics fully coupled model is essential for a reliable prediction of the creep rate and the corresponding lifetime of an operating stack.